2020
DOI: 10.21608/eajbsz.2020.106396
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Graviola (Annona muricata) Leaves Extract Against Cadmium-Induced Testicular Toxicity In Male Albino Rats

Abstract: Graviola (Annona muricata), an edible plant belonging to the Annonaceae family, has a long history in traditional medicine due to its wide range of therapeutic effects on many ailments. This study was planned to assess the protective potentials of Graviola leaves extract (GLE) on cadmiuminduced testicular damage in male albino rats. The study was conducted on 32 male adult Wistar rats randomly divided into four groups (n=8/each). A (control group); B (GLE, 100 mg/kg); C (cadmium chloride (CdCl 2), 5 mg/kg) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
0
0
Order By: Relevance
“…Onyegeme-Okerenta et al(126) and Olowofolahan et al(127) reported a significant decline in FSH level following Annona muricata in reproductive dysfunction, which disagree with the study outcome. The study corroborates the findings of Abd El-Monem and Elwakeel(128) and El-Sawi et al(129), revealing a significantly higher level of FSH following Annona muricata extract against testicular toxicity.…”
supporting
confidence: 91%
“…Onyegeme-Okerenta et al(126) and Olowofolahan et al(127) reported a significant decline in FSH level following Annona muricata in reproductive dysfunction, which disagree with the study outcome. The study corroborates the findings of Abd El-Monem and Elwakeel(128) and El-Sawi et al(129), revealing a significantly higher level of FSH following Annona muricata extract against testicular toxicity.…”
supporting
confidence: 91%
“…A previous study indicated that A. squamosa had broad-spectrum activity against bacterial pathogens, which suggested that it could be used as a food sanitizer [19]. Leaf extract from another member of the Annonaceae family, A. muricata, has been studied for its ability to shield male rats from testicular damage caused by cadmium [20]. It has been reported that A. muricata attenuated testicular oxidative stress in rats [21].…”
Section: Introductionmentioning
confidence: 99%